Victory Day - Rudnitskaya, Alina (Russia, 2014)
In 2013 the Russian Parliament passed a law banning public promotion of non-traditional sexual relations between minors. This law led to the rise of homophobia in the society. The film interviews same-sex couples about life under the anti-homosexual law while, outside of their homes, a military parade is marching through the streets.
Verzio Film Festival Submission
Keywords: Documentary films